Inter‐ and intralaboratory variation of in vitro diffusion cell measurements: An international multicenter study using quasi‐standardized methods and materials - Chilcott, R.P.; Barai, N.; Beezer, A.E.; Brain, S.I.; Brown, M.B.; Bunge, A.L.; Burgess, S.E.; Cross, S.; Dalton, C.H.; Dias, M.; Farinha, A.; Finnin, B.C.; et al. (Journal of Pharmaceutical Sciences, 2005)
In vitro measurements of skin absorption are an increasingly important aspect of regulatory studies, product support claims, and formulation screening. However, such measurements are significantly affected by skin variability. The purpose of this study was to determine inter‐ and intralaboratory variation in diffusion cell measurements caused by factors other than skin. This was attained through the use of an artificial (silicone rubber) rate‐limiting membrane and the provision of materials including a standard penetrant, methyl paraben (MP), and a minimally prescriptive protocol to each of the 18 participating laboratories. “Standardized” calculations of MP flux were determined from the data submitted by each laboratory by applying a predefined mathematical model. This was deemed necessary to eliminate any interlaboratory variation caused by different methods of flux calculations. Average fluxes of MP calculated and reported by each laboratory (60 ± 27 μg cm−2 h−1, n = 25, range 27–101) were in agreement with the standardized calculations of MP flux (60 ± 21 μg cm−2 h−1, range 19–120). The coefficient of variation between laboratories was approximately 35% and was manifest as a fourfold difference between the lowest and highest average flux values and a sixfold difference between the lowest and highest individual flux values. Intralaboratory variation was lower, averaging 10% for five individuals using the same equipment within a single laboratory. Further studies should be performed to clarify the exact components responsible for nonskin‐related variability in diffusion cell measurements. It is clear that further developments of in vitro methodologies for measuring skin absorption are required. © 2005 Wiley‐Liss, Inc. and the American Pharmacists Association J Pharm Sci 94:632–638, 2005